2022
DOI: 10.3389/fonc.2022.963728
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and functional homologous repair deficiency as biomarkers for platinum sensitivity in TNBC: A case report

Abstract: Triple-negative breast cancer is the most aggressive subtype of mammary carcinoma. In the early stage, neoadjuvant chemotherapy (NAC) is the standard of care for prognostic stratification and the best adjuvant treatment strategy. A 30-year-old female presented in the emergency room because of a gigantic right breast associated with an ulcerated lump at the upper quadrants. The right axillary nodes were palpable. An ultrasound was performed, showing the ulcerated neoformation with enlarged right axillary lymph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In ARIEL2, Swisher et al showed that mutations in RAD51C/D were associated with genomic HRD (based on high genomic LOH) and response to the PARP inhibitor rucaparib in 5 of 7 patients (71.4%) with relapsed high-grade ovarian cancer, reaching a median progression-free survival similar to patients with mutated BRCA1/2 . Similarly, one study showed a high sensitivity to DNA-damaging chemotherapy in a patient with breast cancer with a RAD51D germline PV and functional HRD . Overall, prior clinical trials in breast cancer or ovarian cancer have analyzed the efficacy of platinums and PARP inhibitors for patients with germline RAD51C/D PVs observing a wide range of treatment responses .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ARIEL2, Swisher et al showed that mutations in RAD51C/D were associated with genomic HRD (based on high genomic LOH) and response to the PARP inhibitor rucaparib in 5 of 7 patients (71.4%) with relapsed high-grade ovarian cancer, reaching a median progression-free survival similar to patients with mutated BRCA1/2 . Similarly, one study showed a high sensitivity to DNA-damaging chemotherapy in a patient with breast cancer with a RAD51D germline PV and functional HRD . Overall, prior clinical trials in breast cancer or ovarian cancer have analyzed the efficacy of platinums and PARP inhibitors for patients with germline RAD51C/D PVs observing a wide range of treatment responses .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, one study showed a high sensitivity to DNA-damaging chemotherapy in a patient with breast cancer with a RAD51D germline PV and functional HRD. 25 Overall, prior clinical trials in breast cancer or ovarian cancer have analyzed the efficacy of platinums and PARP inhibitors for patients with germline RAD51C/D PVs observing a wide range of treatment responses. 26 , 27 Some studies have reported the presence of gsLOH 26 but lack of concordance with HRD by GIS, and others do not report biallelic inactivation or HRD status.…”
Section: Introductionmentioning
confidence: 99%